Digital-Based Sustainable Tourism Security through Pentahelix Collaboration in Samalona Island, Makassar, Indonesia - ., Seniwati; ., Rahmatia; Amri, Khairul; As’ad, Ihwana; Ranti, Munif Arif (Journal of Ecohumanism, 2024)
Samalona Island is a tourist destination in Makassar City, South Sulawesi Province, Indonesia. This study aims to identify the potential and challenges in developing digital innovation-based tourism on Samalona Island. The potential of Samalona Island includes a sense of security and the beauty of its underwater nature. This island is a favorite place for foreign and domestic tourists because tourists feel safe when visiting the island. The involvement of all actors, such as stakeholders, industry, media, academics, and local communities, supports the development of Samalona Island. The novelty in this study is the lack of articles discussing Samalona Island based on the pentahelix model. This study found that Samalona Island’s development applies the ecotourism principle that focuses on the environment. The role of the media in marketing the potential of Samalona Island attracts domestic and foreign tourists to the island.